The effectiveness of combined local and systemic methotrexate treatment in cesarean scar pregnancy weeks 8 to 14 - Xuyen Van; Thuong Bui; Hoang The Dinh; Thong Van; Anh Tran (Wolters Kluwer Medknow Publications, 2023)
Objectives: This study aims to identify the success rate and correlated factors of combined local and systemic methotrexate (MTX) injection treatment in cesarean scar pregnancy (CSP). Materials and Methods: The combined local and systemic MTX administration has been used for CSP weeks 8-14 at Tu Du Maternal Hospital; however, its effectiveness and correlated factors have not been closely investigated. This is a retrospective case series of 123 CSP patients between 8 and 14 weeks of gestation who were treated at Tu Du Hospital from the year 2016 to 2020. Results: The success rate, uterine-sparing rate, and side effects of MTX treatment are 50.4%, 95%, and 17.2%, respectively. The factors related to treatment failure with statistical significance included gestational age (odds ratio [OR] = 3.99), residual myometrial thickness >3 mm (OR = 0.37), and postprocedure gestational sac diameter (OR = 1.09). Conclusion: Combined local and systemic MTX injection is minimally invasive and effective in CSP weeks 8-14. Therefore, it should be utilized routinely.